ANALISIS PENGARUH KOMPETENSI DAN REWARDS TERHADAP INTENTION QUIT YANG BERDAMPAK PADA KINERJA KARYAWAN HOTEL ASTON SIMATUPANG DAN HOTEL ASTON RASUNA - Permata Sari, Marisa; Irvandi; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2019)
This study aims to conduct a list of analysts that influence the performance of hotel employees in Jakarta. The variables used are Competence, Reward, Intent to quit as independent variables and dependent variables are Performance. The statistical method uses Structural Equation Modeling (SEM). The findings obtained include (1) Competence has a positive and significant effect on Performance (2) Reward has a significant effect on Intent to quit (3) Reward has a positive and significant effect on Performance. (4) Competence does not have a significant effect on Intent to quit (5) Intent to quit does not have a significant effect on Performance, This means that the higher the level of Intent to quit, the significant effect on Performance is not.